2010
DOI: 10.1007/s11148-010-9306-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical properties of refractory materials of AL2O3–Si3N4–C compositions based on acpb after impregnation with a sol-gel composition

Abstract: Comparative characteristics are presented for the physicomechanical properties and oxidation resistance of refractory materials of Al 2 O 3 -Si 3 N 4 -C composition based on an ACPB for the original materials (fired at 1400°C) and after impregnation with a sol-gel composition and heat treatment at 800°C. A reduction in material porosity, increase in strength and reduction in carbon burn-off are due to development of a glassy phase in the pore space and on graphite flakes due to SiO 2 formation with thermal des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Previous researches showed that the suspensions or colloidal solutions impregnation treatment is one of the effective methods to improve microstructure, mechanical properties and thermal insulation performance of refractories. [23][24][25][26][27] Works by Jin et al showed that the impregnated Si 2 N 2 O porous ceramics with silica sol improved the mechanical properties of refractories due to the reduced surface pores and the increased crack propagation paths. 28 Research by Malaiskiene et al presented that the impregnation of silica sol into fireclay-based castables formed a denser and thinner glassy barrier on the sample surface, and further reduced the penetration of potassium-containing liquid phases, significantly improving the corrosion and penetration resistance to alkaline compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researches showed that the suspensions or colloidal solutions impregnation treatment is one of the effective methods to improve microstructure, mechanical properties and thermal insulation performance of refractories. [23][24][25][26][27] Works by Jin et al showed that the impregnated Si 2 N 2 O porous ceramics with silica sol improved the mechanical properties of refractories due to the reduced surface pores and the increased crack propagation paths. 28 Research by Malaiskiene et al presented that the impregnation of silica sol into fireclay-based castables formed a denser and thinner glassy barrier on the sample surface, and further reduced the penetration of potassium-containing liquid phases, significantly improving the corrosion and penetration resistance to alkaline compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches showed that the suspensions or colloidal solutions impregnation treatment is one of the effective methods to improve microstructure, mechanical properties and thermal insulation performance of refractories 23–27 . Works by Jin et al.…”
Section: Introductionmentioning
confidence: 99%